Importance of monovalent ions on water retention capacity of superabsorbent polymer in cement-based solutions. (April 2018) - Kang, Sung-Hoon; Hong, Sung-Gul; Moon, Juhyuk
Abstract: The effects of various ions in cement-based solutions on the water retention capacity and ion absorbency of superabsorbent polymers (SAPs) are studied herein. It is verified that the retention capacity of the SAP is reduced due to the absorbed Ca 2+ from solution, and the SAP releases monovalent cations such as Na + into the solution upon absorption of Ca 2+ . Importantly, it was determined that non-multivalent cations in solutions play a critical role in the retention capacity of SAPs. As the total ion concentration (TIC) of the solution increases, the retention capacity improves. Higher TIC yields a weaker osmotic pressure, which reduces the driving force for the initial absorption of SAP. Therefore, the amount of the Ca 2+ absorbed in the SAP decreases and the retention capacity improves. Based on the accurately measured ionic characteristics during absorption and desorption, the complicated retention phenomenon and its ionic dependence in cement-based solutions are clearly understood.